Penggunaan Model Make a Match untuk Meningkatkan Keterampilan Membuat Pantun di Kelas V Sekolah Dasar - Yulia Meyessy (Universitas Sebelas Maret, 2020)
Learning skills to make rhymes in class V SD Negeri 07 Padang Sarai has not taken place as expected. This can be seen from the low results of rhyme making skills. The Make A Match model was chosen to overcome these problems. This study aims to improve the skills of fifth grade students of SD Negeri 07 Padang Sarai about making rhymes. The make a match model is defined as a learning system that prioritizes the cultivation of social skills, especially the ability to cooperate, the ability to interact in addition to the ability to think quickly through games to find partners with the help of cards. The implementation of the make a match method on the material for making rhymes is done by modifying the question and answer cards into sampiran cards and the contents of the pantun. The cards are shuffled by shuffling before being distributed to students. Each student is given one card, then instructed to form groups of 4 members. If combined, the cards of the four people in the group must contain a rhyme. Each correct group will be given a prize, otherwise the wrong group will be punished according to mutual agreement. This learning model with a game approach will be very interesting for students. The skill of the teacher when designing and implementing the make a match model is the key to the success of learning activities